Emotional Intelligence, Job Engagement, and Employee Performance: The Moderating Role of Perceived Organizational Support - Andi Ira Angraeni Rahman (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study aims to analyze the determinants of employee performance by examining the influence of emotional intelligence and perceived organizational support while evaluating the moderating role of the interaction between these variables and job engagement. Employing a quantitative approach with Partial Least Squares Structural Equation Modeling or SEM PLS analysis techniques, this research involved the entire population of 80 employees at the Health Department of Bombana Regency as respondents selected through saturated sampling method. The statistical analysis results provide empirical evidence that emotional intelligence has a positive and significant impact on employee performance and plays a central role in shaping high job engagement. Conversely perceived organizational support partially proves to have no significant direct effect on performance but the interaction test findings indicate that this variable functions effectively as a moderator that strengthens relationships in the model. Specifically organizational support will only have a tangible impact on performance improvement when synergized with a high level of job engagement. The conclusion of this study emphasizes that to achieve optimal performance the institution needs to prioritize the development of employee emotional maturity while ensuring the existence of targeted organizational support that can strengthen the contribution of employees who already have high dedication to their work.